Η πλοκή στην παιδική και εφηβική αστυνομική μυθοπλασία - Παρασκευή, Αντωνά (Παιδαγωγικά ρεύματα στο Αιγαίο, 2022)
This dissertation is a study of children’s and young adult’s Greek detective novels that have been published during the past decade. The main aim is to present the typology that arises, a typology which is based on the analysis of the plot. Particularly, there was an attempt to identify the stages of the plot and to clarify the basic characteristics of the plot in such texts.